Tradisi Pernikahan Kerubahan Gunung Perspektif Fenomenologi - Sulton Muzadi; Muhammad Solikhudin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
People's views on the value of marriage are considered sacred in life, and Islam upholds a marriage. When a person has fulfilled the requirements of the pillars of marriage, he immediately entered into a marriage contract, because it would be dangerous to delay marriage. However, in Candisari Village, Sambeng District, Lamongan Regency, the phenomenon of the "kerubahan gunung" marriage prohibition occurred. As for the practice of the "kerubahan gunung" tradition, while in the process of waiting for the wedding day, a family member, especially a straight line parent, died before the day of the wedding ceremony. So when following the tradition, the marriage must be postponed to next year or the turn of the Javanese year, namely the suro month. he settlement pattern is to do two ways by doing the marriage next to the corpse or by delaying the marriage by waiting for next year. The phenomenological correlation in the pattern of settlement of the "kerubuhan gunung" tradition by bringing up three aspects: First, the phenomenon, digging information, observing and collecting tradition data. Second, awareness, uniting the heart, mind and the five senses to understand tradition. and third, the constitution, confirms and narrates the meanings behind the "kerubahan gunung" marriage tradition. Thus, this pattern of settlement is in accordance with 'urf shahih and fiqh rules which read that rejecting damage takes precedence over attracting benefit.